High-cohesiveness polyimide composite film capable of being used for flexible copper-clad plate and preparation method of high-cohesiveness polyimide composite film

By inserting end amino hyperbranched polyamide grafted silica particles between the thermoset polyimide support layer and the thermoplastic polyimide bonding layer of the flexible copper clad plate to form an interface layer, the problem of difficulty in achieving high bonding, high dimensional stability, high heat resistance and low glass transition temperature in the prior art is solved, and a high-performance flexible copper clad plate film is realized.

CN119858367AActive Publication Date: 2025-04-22ZHUZHOU TIMES HUAXIN NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510352379.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to achieve comprehensive properties of high adhesion, high dimensional stability, high heat resistance and low glass transition temperature in flexible copper laminates.

Method used

An interface layer is formed to improve adhesion and dimensional stability by providing a thermoplastic polyimide bonding layer on at least one side of the thermoset polyimide support layer and embedded end amino hyperbranched polyamide grafted silica particles between the two.

Benefits of technology

It significantly improves the adhesion, dimensional stability and heat resistance of the composite film, while maintaining a low glass transition temperature, meeting the high performance needs of flexible copper clad plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858367A_ABST
    Figure CN119858367A_ABST
Patent Text Reader

Abstract

The invention discloses a high-cohesiveness polyimide composite film capable of being used for a flexible copper-clad plate and a preparation method of the high-cohesiveness polyimide composite film. The polyimide composite film is composed of a thermosetting polyimide supporting layer and a thermoplastic polyimide bonding layer arranged on at least one face of the thermosetting polyimide supporting layer. An interface layer formed by reacting amino-terminated hyperbranched polyamide grafted silicon dioxide particles with thermosetting polyamide acid is embedded between the thermosetting polyimide supporting layer and the thermoplastic polyimide bonding layer, and an end group of thermoplastic polyimide contains an imidazole ring capable of forming a complex with copper. The amino-terminated hyperbranched polyamide grafted silicon dioxide particles are embedded into the interface of the thermosetting layer and the thermoplastic layer, so that the contact area of the supporting layer and the adhesive layer is increased; the polyimide composite film with high cohesiveness, high dimensional stability, high heat resistance and low glass transition temperature is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyimide films, and in particular relates to a high-adhesion polyimide composite film that can be used for flexible copper-clad laminates and a preparation method thereof. Background Art

[0002] Flexible printed circuit boards (FPCs) are widely used in electronic products, home appliances, medical, automotive, aerospace and military fields due to their light weight, thin thickness and free bending and folding. Flexible copper clad laminates (FCCLs) are the key substrates of FPCs. Traditional three-layer FCCLs are composed of copper foil, thermosetting polyimide film and epoxy or silicone adhesives, while two-layer FCCLs use thermoplastic polyimide layers instead of epoxy or silicone adhesives, making copper clad laminates lighter, thinner and more heat-resistant, and gradually becoming the mainstream of the industry.

[0003] Chinese patent application document CN103739842A proposes a thermoplastic polyimide film for two-layer FCCL. In order to ensure a certain dimensional stability, diamines containing benzoxazole, benzimidazole aromatic heterocycles, etc. are introduced, which reduces the thermoplasticity of the overall molecular chain, resulting in an adhesion of only 1.1-1.2N / mm, which brings hidden dangers to subsequent applications.

[0004] Chinese patent application document CN115746351A proposes a method for preparing a thermoplastic polyimide film with a low thermal expansion coefficient. The thermal expansion coefficient of the film is reduced by introducing double bonds into the polyimide molecular chain and achieving photocrosslinking under the action of a crosslinking agent and a photoinitiator. However, the crosslinking structure restricts the movement of the molecular chain, making its glass transition temperature close to 300°C, which is not conducive to hot pressing processing and difficult to commercialize.

[0005] Chinese patent application document CN1957051A proposes an adhesive film and a preparation method thereof, which uses a co-extrusion-cast coating method to composite a thermoplastic polyimide adhesive layer on one or both sides of a thermosetting polyimide core layer to obtain a heat-bondable composite film. However, both thermosetting and thermoplastic polyamic acid precursors use diamine or dianhydride condensation. The end group is an amino group, which will cause oxidation when heated, reducing the heat resistance of the film, especially the adhesion after heating. The end group is an anhydride group, which is prone to ring-opening hydrolysis, resulting in uneven distribution of polyimide molecular weight, thereby affecting the uniformity of performance.

[0006] From the above, it can be seen that in order to meet the performance requirements of high adhesion, high dimensional stability, high heat resistance and low glass transition temperature of the two-layer FCCL for the film substrate, it is necessary to improve the existing technology to meet the increasingly stringent application requirements. Summary of the invention

[0007] In order to overcome the problems in the prior art, the present invention provides a high-adhesion polyimide composite film that can be used for flexible copper-clad laminates and a preparation method thereof, to prepare a polyimide composite film with high adhesion, high dimensional stability, high heat resistance and low glass transition temperature.

[0008] In order to solve the above technical problems, the technical solution proposed by the present invention is: The invention provides a highly adhesive polyimide composite film for a flexible copper-clad laminate, wherein the polyimide composite film comprises a thermosetting polyimide support layer and a thermoplastic polyimide adhesive layer arranged on at least one side of the thermosetting polyimide support layer, and an interface layer formed by the reaction of amino-terminated hyperbranched polyamide grafted silica particles and thermosetting polyamic acid is embedded between the thermosetting polyimide support layer and the thermoplastic polyimide adhesive layer.

[0009] In the present invention, amino-terminated hyperbranched polyamide grafted silica particles are embedded in the interface of the thermosetting layer and the thermoplastic layer to increase the contact area between the support layer and the adhesive layer, thereby improving the peeling force of the composite film and increasing the adhesion.

[0010] As an optional embodiment, in the polyimide composite film provided by the present invention, the interface layer is formed by dispersing the amino-terminated hyperbranched polyamide grafted silica particles in a chemical casting reagent, mixing them with a thermosetting polyamide acid resin, and then obtaining them through a polymerization reaction.

[0011] As an optional embodiment, in the polyimide composite film provided by the present invention, the thermosetting polyimide support layer is prepared by reacting a flexible aromatic diamine and a rigid aromatic diamine with an aromatic dianhydride, and the molar ratio of the flexible aromatic diamine to the rigid aromatic diamine is 5-35:65-95.

[0012] The precursor polyamic acid resin in the present invention is prepared by polycondensation reaction of flexible aromatic diamine, rigid aromatic diamine and aromatic dianhydride. The use of rigid aromatic diamine monomer can reduce the linear expansion coefficient, and the close stacking of molecules can control the water absorption rate, thereby reducing the risk of delamination and explosion of copper clad laminates caused by film moisture absorption. However, too much rigid aromatic diamine will cause the flexibility of the film to continue to decrease, which cannot meet the application requirements. Therefore, the present invention also simultaneously introduces a flexible aromatic diamine monomer to increase the elongation and improve the application performance.

[0013] As an optional implementation, in the polyimide composite film provided by the present invention, the end group of the thermoplastic polyimide adhesive layer contains an imidazole ring that can form a complex with copper.

[0014] Based on the same technical concept, the present invention also provides a method for preparing the highly adhesive polyimide composite film for the above-mentioned flexible copper-clad laminate, comprising the following steps: S1. Polyamide acid resin A is generated by polycondensing a flexible aromatic diamine, a rigid aromatic diamine and an aromatic dianhydride.

[0015] S2, allowing the surface aminated silica to undergo an addition reaction with acrylate or its homologues, and then reacting with aliphatic diamine or its homologues to obtain amino-terminated hyperbranched polyamide grafted silica particles, and finally dispersing them in a chemical casting reagent, and quickly mixing them with the polyamic acid resin A prepared in step S1 to obtain a mixed solution; the mass ratio of the surface aminated silica, acrylate or its homologues and aliphatic diamine or its homologues is 1:1-3:0.7-4.

[0016] S3, polyamic acid resin B is generated by polycondensing diamine, dianhydride and monoamine.

[0017] S4, using the mixed solution in step S2 as a thermosetting polyimide support layer and the polyamic acid resin B prepared in step S3 as a thermoplastic polyimide adhesive layer, and preparing a polyimide composite film through a film-forming process.

[0018] In the present invention, the degree of branching of the amino-terminated hyperbranched polyamide grafted silica particles is controlled by controlling the amount of acrylate or its homologues and aliphatic diamine or its homologues. If the degree of branching is too small, the number of amino groups is small, and the compatibility with the resin is not significantly improved; if the degree of branching is large, the polymer cross-linking is caused, and the film performance is also affected. The amino-terminated hyperbranched polyamide grafted silica particles are dispersed in a chemical casting reagent and mixed with a thermosetting polyamic acid resin, wherein the liquid chemical casting reagent can significantly reduce the resin viscosity, which is helpful for the amino-terminated hyperbranched polyamide grafted silica particles to be uniformly dispersed; the chemical casting reagent is used to promote the gelation of the resin in a short time, lock the distribution of the amino-terminated hyperbranched polyamide grafted silica particles in the film, and avoid the sedimentation and secondary agglomeration of the amino-terminated hyperbranched polyamide grafted silica particles caused by too long storage or reaction time; the unique hyperbranched molecular structure, low chain entanglement and a large number of amino groups on the silica surface can enhance the compatibility of the silica inorganic particles with the organic system. During high-speed mixing and film casting, it reacts with the terminal anhydride groups of the thermosetting polyamic acid molecular chain to eliminate residual active groups and form a cross-linked network structure to improve the dimensional stability and heat resistance of the film. In the field of chemistry, homologous series refer to organic compounds with similar structures and molecular compositions that differ by one or more "CH2" atomic groups.

[0019] As an optional embodiment, in the preparation method provided by the present invention, in step S2, the added amount of the amino-terminated hyperbranched polyamide grafted silica particles is 0.05-1% of the mass of the thermosetting polyimide support layer, and the particle size of the amino-terminated hyperbranched polyamide grafted silica particles is 0.1-10 μm.

[0020] Furthermore, the particle size of the amino-terminated hyperbranched polyamide grafted silica particles is preferably 0.2-6 μm.

[0021] In the present invention, the amount of the amino-terminated hyperbranched polyamide grafted silica particles added is calculated based on the total amount of powder input. By controlling the particle size and amount of the amino-terminated hyperbranched polyamide grafted silica particles, the amino-terminated hyperbranched polyamide grafted silica particles are embedded in the interface of the thermosetting layer and the thermoplastic layer, thereby increasing the contact area between the support layer and the adhesive layer and improving the peeling force of the composite film without affecting other properties.

[0022] As an optional embodiment, in the preparation method provided by the present invention, in step S2, the chemical casting reagent is composed of a catalyst, a dehydrating agent and an organic solvent; the catalyst is selected from one or more of pyridine and its derivatives, quinoline, isoquinoline and triethylamine, and the amount of the catalyst is 1-5% of the mass of the polyamic acid resin A; the dehydrating agent is selected from one or more of acetic anhydride, propionic anhydride and benzoic anhydride, and the amount of the dehydrating agent is 15-35% of the mass of the polyamic acid resin A. In the field of chemistry, a derivative refers to a more complex product derived from the replacement of atoms or atomic groups in a compound molecule by other atoms or atomic groups, or it can be a new substance generated by the transformation of the original substance through a chemical reaction.

[0023] As an optional embodiment, in the preparation method provided by the present invention, the film forming process in step S4 includes the following steps: using the mixed solution in step S2 as the support layer, and using the polyamic acid resin B prepared in step S3 as the bonding layer, and then subjecting the two-layer or three-layer co-extrusion die to high-temperature treatment to obtain a polyimide composite film.

[0024] As an optional embodiment, in the preparation method provided by the present invention, the film forming process in step S4 also includes the following steps: preparing a thermosetting polyimide support layer by a chemical casting method, and then coating a polyamic acid resin B on one or both sides, and preparing a polyimide composite film by high-temperature imidization.

[0025] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the molar ratio of the sum of the molar amounts of the flexible aromatic diamine and the rigid aromatic diamine to the molar amount of the aromatic dianhydride is 100:100.05-100.5.

[0026] As an optional embodiment, in the preparation method provided by the present invention, the monoamine is a monoamine containing an imidazole structure.

[0027] As an optional embodiment, in the preparation method provided by the present invention, the monoamine containing an imidazole structure is selected from one or more of 2-aminoimidazole, 4-aminoimidazole, 5-amino-4-imidazolecarboxamide, and 2-aminobenzimidazole; the molar ratio of the diamine, dianhydride and the monoamine containing an imidazole structure is 98-99.5:100:0.5-4.

[0028] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the molar ratio of the sum of the molar amounts of the flexible aromatic diamine and the rigid aromatic diamine to the molar amount of the aromatic dianhydride is 100:100.05-100.5.

[0029] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the flexible aromatic diamine is selected from one or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and 2,2-bis[4-(4-aminophenoxy)phenyl]propane.

[0030] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the rigid aromatic diamine is selected from one or more of 4,4'-diaminobiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, p-phenylenediamine, m-phenylenediamine, p-phenylenediamine and 4,4'-diaminobenzophenone.

[0031] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the aromatic dianhydride is selected from one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride and 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride.

[0032] As an optional embodiment, in the preparation method provided by the present invention, in step S3, the diamine is selected from one or more of 4,4'-diaminodiphenyl ether (4,4'-ODA), 3,4'-diaminodiphenyl ether (3,4'-ODA), 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (TPE-M), 1,4-bis(4-aminophenoxy)benzene (TPE-Q), 4,4'-bis(4-aminophenoxy)diphenyl sulfone (BAPS) and 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP).

[0033] As an optional embodiment, in the preparation method provided by the present invention, in step S3, the dianhydride is selected from one or more of pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,3,3',4'-biphenyltetracarboxylic dianhydride (α-BPDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA) and 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride (α-ODPA).

[0034] Based on the same technical concept, the present invention also provides a two-layer flexible copper clad laminate, comprising a copper foil layer and a polyimide layer, wherein the polyimide layer is the above-mentioned high-adhesion polyimide composite film.

[0035] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, a thermoplastic polyimide adhesive layer is provided on at least one side of the thermosetting polyimide support layer, and an interface layer formed by the reaction of amino-terminated hyperbranched polyamide grafted silica particles is embedded between the thermosetting polyimide support layer and the thermoplastic polyimide adhesive layer, thereby increasing the contact area between the support layer and the adhesive layer, improving the peeling force of the composite film, and increasing the adhesion.

[0036] (2) In the present invention, the amino-terminated hyperbranched polyamide grafted silica particles are mixed with a chemical casting reagent and a thermosetting polyamic acid resin solution, so that the inorganic particles can be evenly distributed in the film, thereby avoiding the occurrence of sedimentation and agglomeration problems; at the same time, the amino-terminated hyperbranched polyamide grafted silica particles have a large number of amino groups on the surface, which can enhance the compatibility of the silica particles with the organic system; during high-speed mixing and casting film formation, they react with the terminal anhydride groups of the thermosetting polyamic acid molecular chain to eliminate residual active groups, and can also form a cross-linked network structure, thereby improving the dimensional stability of the film.

[0037] (3) The monoamine containing imidazole structure in the present invention is used as an end-capping agent for thermoplastic polyamic acid. On the one hand, it can control the end point of the polycondensation reaction, avoid excessive growth of the molecular chain in the later stage, and improve the uniformity of the molecular weight distribution. On the other hand, it can form a complex with copper through the imidazole ring, which can improve the adhesion of the composite film. Moreover, the imidazole ring is introduced as an end group, which accounts for a small proportion in the molecular chain and will not reduce the overall thermoplasticity.

[0038] (4) The present invention can significantly improve the material's adhesion, dimensional stability, heat resistance and other properties by further optimizing the film, while maintaining a low glass transition temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The results of microscopic examination of the polyimide composite film prepared in Example 7; Figure 2 Schematic diagram of the reaction of amino-terminated hyperbranched polyamide grafted silica particles prepared in the example; Figure 3 The plan view of the polyimide composite film prepared in Comparative Example 1, the left side is the result of observation under a 500x microscope, and the right side is the result of observation under a 1500x microscope; Figure 4 The plan view of the layer film of the polyimide composite film prepared in Example 3, the left side is the result of observation under a 500x microscope, and the right side is the result of observation under a 1500x microscope; Figure 5 This is a plan view of the layer film of the polyimide composite film prepared in Comparative Example 3, the left side is the result of observation under a 500x microscope, and the right side is the result of observation under a 1500x microscope. DETAILED DESCRIPTION

[0040] For the convenience of understanding the present invention, the present invention will be described more comprehensively and meticulously in conjunction with the accompanying drawings and preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all professional terms used hereinafter have the same meaning as those skilled in the art generally understand. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.

[0041] Example 1 The method for preparing a highly adhesive polyimide composite film comprises the following steps: 1. Aggregation 31.7 kg of ODA and 36.4 kg of p-PDA were dissolved in 800 kg of dimethylformamide, and 54.4 kg of PMDA, 31.9 kg of BTDA and 43.7 kg of BPDA were added in batches and reacted for 5 hours to obtain a thermosetting polyamic acid resin with a viscosity of 1850P.

[0042] 11.7 kg of ODA and 31.2 kg of TPE-R were dissolved in 420 kg of dimethylformamide, 36.4 kg of PMDA was added in batches, and finally 0.48 kg of 2-aminoimidazole was added to react for 4 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 550P.

[0043] Add 1 kg of amino-modified silica with a particle size of 0.4 μm and 2.2 kg of methyl acrylate to 10 kg of methanol, react at 50°C and then vacuum filter, then add 3.35 kg of ethylenediamine, react in methanol and vacuum filter to obtain amino-terminated hyperbranched polyamide grafted silica particles. The reaction diagram is shown in the figure below. Figure 2 shown.

[0044] 2. Film making 1.6 kg of amino-terminated hyperbranched polyamide grafted silica particles, 19 kg of pyridine, and 22 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamide acid resin at a rotation speed of 1850 rpm. The mixture was transported to the die head through a pipeline and extruded. Then, a thermosetting polyimide film with a thickness of 19 μm was obtained through processes such as casting, longitudinal and transverse stretching, and high-temperature heating.

[0045] 3. Coating Thermoplastic polyamic acid resin is coated on both sides of the thermosetting polyimide film, and the temperature is programmed to rise within the range of 150°C-450°C to obtain a composite film with a total thickness of 25 μm, and the thickness of the adhesive layer on both sides is 3 μm respectively.

[0046] Example 2 The method for preparing a highly adhesive polyimide composite film comprises the following steps: The polymerization process is the same as in Example 1.

[0047] 1.58 kg of amino-terminated hyperbranched polyamide grafted silica particles with a particle size of 0.5 μm, 18 kg of pyridine, and 21 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 1850 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head with a thermoplastic polyamic acid resin for extrusion molding, and then subjected to processes such as casting, longitudinal and transverse stretching, and high-temperature heating to obtain a composite film with a total thickness of 25 μm, and the thickness of the adhesive layer on both sides was 3 μm respectively.

[0048] Example 3 The method for preparing a highly adhesive polyimide composite film comprises the following steps: 1. Aggregation 12.7 kg of ODA, 12.4 kg of TPE-M and 67.5 kg of 4,4'-diamino-2,2'-dimethylbiphenyl were dissolved in 800 kg of dimethylformamide, and 65.2 kg of PMDA and 41 kg of BTDA were added in batches and reacted for 6 hours to obtain a thermosetting polyamic acid resin with a viscosity of 2370P.

[0049] 14.4 kg of ODA and 25.9 kg of BAPP were dissolved in 420 kg of dimethylformamide, 9.4 kg of PMDA and 29.6 kg of α-BPDA were added in batches, and finally 0.57 kg of 2-aminobenzimidazole was added to react for 4.5 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 510P.

[0050] Add 1 kg of amino-modified silica with a particle size of 3 μm and 2.2 kg of methyl acrylate to 10 kg of methanol, react at 50°C and then vacuum filter, then add 3.35 kg of ethylenediamine, react in methanol and vacuum filter to obtain amino-terminated hyperbranched polyamide grafted silica particles. The reaction diagram is shown in the figure below. Figure 2 shown.

[0051] 2. Film making 1 kg of amino-terminated hyperbranched polyamide grafted silica particles, 19 kg of pyridine and 22 kg of acetic anhydride were added into a high-speed mixer, mixed evenly with the resin at a speed of 2250 rpm, transported to the die head through a pipeline, extruded and then subjected to processes such as casting, longitudinal and transverse stretching, and high-temperature heating to obtain a thermosetting polyimide film with a thickness of 19 μm.

[0052] 3. Coating Thermoplastic polyamic acid resin is coated on both sides of the thermosetting polyimide film, and the temperature is programmed to rise within the range of 150°C-450°C to obtain a composite film with a total thickness of 25 μm, and the thickness of the adhesive layer on both sides is 3 μm respectively.

[0053] Example 4 The method for preparing a highly adhesive polyimide composite film comprises the following steps: The polymerization process is the same as in Example 2.

[0054] 1 kg of amino-terminated hyperbranched polyamide grafted silica particles with a particle size of 3.2 μm, 19 kg of pyridine, and 22 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 2350 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head with a thermoplastic polyamic acid resin for extrusion molding, and then subjected to processes such as casting, longitudinal and transverse stretching, and high-temperature heating to obtain a composite film with a total thickness of 25 μm, and the thickness of the adhesive layer on both sides was 3 μm respectively.

[0055] Example 5 The method for preparing a highly adhesive polyimide composite film comprises the following steps: 1. Aggregation 18.2 kg of BAPP, 8.9 kg of 3,4'-ODA and 75.3 kg of 4,4'-diamino-3,3'-dimethylbiphenyl were dissolved in 800 kg of dimethylformamide, and 97.2 kg of PMDA was added in batches to react for 4 hours to obtain a thermosetting polyamic acid resin with a viscosity of 1580P.

[0056] 35.3 kg of BAPS and 10.7 kg of BAPP were dissolved in 420 kg of dimethylformamide, 16.9 kg of ODPA and 16.0 kg of BPDA were added in batches, and finally 0.23 kg of 3-aminoimidazole was added to react for 5.5 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 450P.

[0057] Add 1 kg of amino-modified silica with a particle size of 2.8 μm and 2.2 kg of methyl acrylate to 10 kg of methanol, react at 50°C and then vacuum filter, then add 3.35 kg of ethylenediamine, react in methanol and vacuum filter to obtain amino-terminated hyperbranched polyamide grafted silica particles. The reaction diagram is shown in the figure below. Figure 2 shown.

[0058] 2. Film making 0.4 kg of amino-terminated hyperbranched polyamide grafted silica particles, 19 kg of pyridine and 22 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 2550 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head with a thermoplastic polyamic acid resin for extrusion molding. After casting, longitudinal and transverse stretching, high-temperature heating and other processes, a composite film with a total thickness of 25 μm was obtained, and the thickness of the adhesive layer on both sides was 4 μm respectively.

[0059] Example 6 The method for preparing a highly adhesive polyimide composite film comprises the following steps: 1. Aggregation 10.2 kg of BAPS, 16.1 kg of BAPP and 69.9 kg of 4,4'-diaminobenzophenone were dissolved in 800 kg of dimethylformamide, and 69.4 kg of BPDA and 34.2 kg of PMDA were added in batches and reacted for 6 hours to obtain a thermosetting polyamic acid resin with a viscosity of 2030P.

[0060] 8.9 kg of BAPS and 33.7 kg of TPE-Q were dissolved in 420 kg of dimethylformamide, 15 kg of PMDA and 22.1 kg of BTDA were added in batches, and finally 0.18 kg of 2-aminobenzimidazole was added to react for 5.5 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 620P.

[0061] 1 kg of amino-modified silica with a particle size of 1.5 μm and 2.2 kg of methyl acrylate were added to 10 kg of methanol, reacted at 50° C. and then vacuum filtered. Then 3.35 kg of ethylenediamine was added, reacted in methanol and vacuum filtered to obtain amino-terminated hyperbranched polyamide grafted silica particles.

[0062] 2. Film making 0.2 kg of amino-terminated hyperbranched polyamide grafted silica particles, 19 kg of pyridine and 22 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 2550 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head with a thermoplastic polyamic acid resin for extrusion molding, and then subjected to processes such as casting, longitudinal and transverse stretching, and high-temperature heating to obtain a composite film with a total thickness of 20 μm, and the thickness of the adhesive layer on both sides was 3 μm respectively.

[0063] Example 7 The method for preparing a highly adhesive polyimide composite film comprises the following steps: 1. Aggregation 9.3 kg of TPE-M and 72.8 kg of 4,4'-diaminodiphenylmethane were dissolved in 800 kg of dimethylacetamide, and 117.8 kg of BPDA was added in batches and reacted for 7 hours to obtain a thermosetting polyamic acid resin with a viscosity of 1730P.

[0064] 44.2 kg of TPE-M was dissolved in 420 kg of dimethylacetamide, and 16.6 kg of PMDA, 14.2 kg of α-ODPA and 4.9 kg of BTDA were added in batches, and finally 0.14 kg of 2-aminobenzimidazole was added and reacted for 4.7 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 520P.

[0065] Add 1 kg of amino-modified silica with a particle size of 1 μm and 2.2 kg of methyl acrylate to 10 kg of methanol, react at 50°C and then vacuum filter, then add 3.35 kg of ethylenediamine, react in methanol and vacuum filter to obtain amino-terminated hyperbranched polyamide grafted silica particles. The reaction diagram is shown in the figure below. Figure 2 shown.

[0066] 2. Film making 0.14 kg of amino-terminated hyperbranched polyamide grafted silica particles, 19 kg of pyridine and 22 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 2650 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head with a thermoplastic polyamic acid resin for extrusion molding, and then subjected to processes such as casting, longitudinal and transverse stretching, and high-temperature heating to obtain a composite film with a total thickness of 25 μm, and the thickness of the adhesive layer on both sides was 3 μm respectively.

[0067] Comparative Example 1 The difference from Example 1 is that no 2-aminoimidazole is added, and no amino-terminated hyperbranched polyamide grafted silica particles are added. The rest is the same as in Example 1.

[0068] Comparative Example 2 1. Aggregation 85.8 kg of ODA was dissolved in 800 kg of dimethylacetamide, and 47.1 kg of PMDA, 27.6 kg of BTDA and 37.8 kg of BPDA were added in batches and reacted for 6 hours to obtain a thermosetting polyamic acid resin with a viscosity of 2030P.

[0069] 11.7 kg of ODA and 31.3 kg of TPE-R were dissolved in 420 kg of dimethylacetamide, 36.5 kg of PMDA was added in batches, and finally 0.48 kg of 2-aminoimidazole was added and reacted for 4.5 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 580P.

[0070] 1 kg of amino-modified silica with a particle size of 11.5 μm and 2.2 kg of methyl acrylate were added to 10 kg of methanol, reacted at 50° C. and then vacuum filtered. Then 3.35 kg of ethylenediamine was added, reacted in methanol and vacuum filtered to obtain amino-terminated hyperbranched polyamide grafted silica particles.

[0071] 2. Film making 1.6 kg of amino-terminated hyperbranched polyamide grafted silica particles, 18 kg of pyridine and 21 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 2250 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head with a thermoplastic polyamic acid resin for extrusion molding. After casting, longitudinal and transverse stretching, high-temperature heating and other processes, a composite film with a total thickness of 25 μm was obtained, and the thickness of the adhesive layer on both sides was 3 μm respectively.

[0072] Comparative Example 3 1. Aggregation 55.4 kg of m-PDA was dissolved in 770 kg of dimethylacetamide, and 56.3 kg of PMDA, 33 kg of BTDA and 45.2 kg of BPDA were added in batches and reacted for 6.5 hours to obtain a thermosetting polyamic acid resin with a viscosity of 2350P.

[0073] 10.7 kg of ODA and 30.7 kg of TPE-M were dissolved in 420 kg of dimethylacetamide, 37.5 kg of PMDA was added in batches, and finally 1.142 kg of 2-aminoimidazole was added to react for 4.5 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 580P.

[0074] 1 kg of amino-modified silica with a particle size of 3.5 μm and 2.2 kg of methyl acrylate were added to 10 kg of methanol, reacted at 50° C. and then vacuum filtered. Then 3.35 kg of ethylenediamine was added, reacted in methanol and vacuum filtered to obtain amino-terminated hyperbranched polyamide grafted silica particles.

[0075] 2. Film making 3 kg of amino-terminated hyperbranched polyamide grafted silica particles, 18 kg of pyridine and 21 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 2250 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head and extruded together with the thermoplastic polyamic acid resin. After casting, longitudinal and transverse stretching, high-temperature heating and other processes, a composite film with a total thickness of 25 μm was obtained, and the thickness of the adhesive layer on both sides was 3 μm respectively.

[0076] Comparative Example 4 1. Aggregation 85.8 kg of ODA was dissolved in 770 kg of dimethylacetamide, and 47.1 kg of PMDA, 27.6 kg of BTDA and 37.8 kg of BPDA were added in batches and reacted for 5.8 hours to obtain a thermosetting polyamic acid resin with a viscosity of 1750P.

[0077] 22.2 kg of ODA and 20.7 kg of BAPP were dissolved in 420 kg of dimethylacetamide, 36.7 kg of PMDA was added in batches, and finally 0.419 kg of 2-aminoimidazole was added and reacted for 3 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 500P.

[0078] 1 kg of amino-modified silica with a particle size of 3.5 μm and 2.2 kg of methyl acrylate were added to 10 kg of methanol, reacted at 50° C. and then vacuum filtered. Then 3.35 kg of ethylenediamine was added, reacted in methanol and vacuum filtered to obtain amino-terminated hyperbranched polyamide grafted silica particles.

[0079] 2. Film making 1.6 kg of amino-terminated hyperbranched polyamide grafted silica particles, 18 kg of pyridine and 21 kg of acetic anhydride were added into a high-speed mixer, and mixed evenly with the thermosetting polyamic acid resin at a rotation speed of 2030 rpm to obtain a thermosetting polyamic acid precursor resin, which was simultaneously conveyed to a three-layer co-extrusion die head with a thermoplastic polyamic acid resin for extrusion molding. After casting, longitudinal and transverse stretching, high-temperature heating and other processes, a composite film with a total thickness of 25 μm was obtained, and the thickness of the adhesive layer on both sides was 3 μm respectively.

[0080] Comparative Example 5 The difference from Example 1 is that the amino-terminated hyperbranched polyamide grafted silica particles are not added, and the rest is the same as in Example 1.

[0081] Comparative Example 6 1. Aggregation 31.7 kg of ODA and 36.4 kg of p-PDA were dissolved in 800 kg of dimethylformamide, and 54.4 kg of PMDA, 31.9 kg of BTDA and 43.7 kg of BPDA were added in batches and reacted for 5 hours to obtain a thermosetting polyamic acid resin with a viscosity of 1850P.

[0082] 11.7 kg of ODA and 31.2 kg of TPE-R were dissolved in 420 kg of dimethylformamide, 36.4 kg of PMDA was added in batches, and finally 0.48 kg of 2-aminoimidazole was added to react for 4 hours to obtain a thermoplastic polyamic acid resin with a viscosity of 550P.

[0083] 1 kg of amino-modified silica with a particle size of 0.5 μm and 3.8 kg of methyl acrylate were added to 10 kg of methanol, reacted at 50° C. and then vacuum filtered. Then 3 kg of ethylenediamine was added, reacted in methanol and vacuum filtered to obtain amino-terminated hyperbranched polyamide grafted silica particles.

[0084] The remaining steps are the same as in Example 1.

[0085] Comparative Example 7 The difference from Example 1 is that 2-aminoimidazole is not added, and the rest is the same as in Example 1.

[0086] Performance Testing The polyimide composite film prepared in Example 7 was examined using a microscope, and its cross section was as follows: Figure 1 As shown, the core layer is a thermosetting polyimide layer 1, and the two sides are thermoplastic polyimide layers 2, which are interlaced to form an interface layer 3, and amino-terminated hyperbranched polyamide grafted silica particles 4 are distributed inside.

[0087] The polyimide composite films prepared in Comparative Example 1, Example 3 and Comparative Example 3 were examined using a microscope. The plane of the core layer film was as follows: Figure 3-5 As shown. In Comparative Example 1, no amino-terminated hyperbranched polyamide grafted silica particles were added. Figure 3 It can be obtained that the surface of the core layer is smooth; Figure 4 is the film plane of the polyimide composite film in Example 3, Figure 5 The film plane of the polyimide composite film in Comparative Example 3 shows that as the amount of amino-terminated hyperbranched polyamide grafted silica particles added increases, the surface of the core layer becomes significantly roughened, thereby increasing the contact area between the core layer and the adhesive layer, thereby achieving the effect of improving the peel strength.

[0088] The polyimide films prepared in the above embodiments and comparative examples were tested for mechanical properties according to ASTM D882, linear expansion coefficient according to TMA method, and glass transition temperature according to DMA method (heating rate 5°C / min). They were respectively rolled with 18μm rolled copper foil according to industrial methods to form two-layer glue-free double-sided copper clad laminates, and the peel strength was tested according to IPC-TM-650. The results are shown in Table 1 below.

[0089] Table 1: Comprehensive properties of the polyimide films obtained in the examples and comparative examples

[0090] When the peel strength of Comparative Example 6 was tested, the film broke brittlely and no specific value could be obtained.

[0091] As shown in Table 1, compared with Example 1, no amino-terminated hyperbranched polyamide grafted silica particles and 2-aminoimidazole were used in Comparative Example 1, which slightly increased the thermal expansion coefficient (CTE) of the film and greatly reduced the peel strength. In Comparative Example 2, the thermosetting layer diamine was all flexible ODA and 11.5 μm amino-modified silica was used, resulting in insufficient rigidity of the molecular chain, and the silica particle size was too large, which significantly reduced the mechanical properties of the prepared polyimide film and increased the thermal expansion coefficient (CTE). In Comparative Example 3, the thermosetting layer diamine was all rigid PDA, the regularity of the molecular chain was high, the intermolecular force was increased, the internal rotation and movement of the molecular chain were hindered, and too much silica particles were added, which caused the flexibility of the film to drop sharply and could not meet the application requirements. In Comparative Example 4, the thermosetting layer was all flexible ODA, and the content was too much, which resulted in a decrease in the tensile strength of the film, poor dimensional stability, and too high Tg of the thermoplastic layer, resulting in poor peeling force. In Comparative Example 5, no amino-terminated hyperbranched polyamide was used to graft silica particles, and the thermal expansion coefficient of the film increased, and the peel strength decreased sharply. In Comparative Example 6, methyl acrylate and ethylenediamine were used in large amounts, hyperbranching was excessive, and there were too many amino groups on the surface of the silica particles, resulting in excessive cross-linking of PI, which greatly reduced the elongation of the film and made it easy to break during processing and application. In Comparative Example 7, no 2-aminoimidazole was used in the thermoplastic layer, resulting in a decrease in the peel strength of the film.

[0092] As can be seen from the above, the monoamine containing imidazole structure and the amino-terminated hyperbranched polyamide grafted silica particles are introduced into the structure of the polyimide composite film in the present invention, which can significantly improve the adhesion, dimensional stability and heat resistance of the film, while maintaining a low glass transition temperature, meeting the processing and application requirements of materials such as two-layer FCCL.

[0093] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A highly adhesive polyimide composite film that can be used for a flexible copper-clad laminate, the polyimide composite film comprising a thermosetting polyimide support layer and a thermoplastic polyimide adhesive layer disposed on at least one side of the thermosetting polyimide support layer, characterized in that: An interface layer formed by the reaction of amino-terminated hyperbranched polyamide grafted silica particles and thermosetting polyamic acid is embedded between the thermosetting polyimide support layer and the thermoplastic polyimide bonding layer.

2. The high-adhesive polyimide composite film according to claim 1, characterized in that: The interface layer is formed by dispersing the amino-terminated hyperbranched polyamide grafted silica particles in a chemical casting reagent, mixing the particles with a thermosetting polyamide acid resin, and then performing a polymerization reaction to obtain the interface layer.

3. The high-adhesive polyimide composite film according to claim 1, characterized in that: The thermosetting polyamic acid resin is prepared by reacting a flexible aromatic diamine, a rigid aromatic diamine and an aromatic dianhydride, and the molar ratio of the flexible aromatic diamine to the rigid aromatic diamine is 5-35:65-95.

4. The high-adhesive polyimide composite film according to claim 1, characterized in that: The terminal group of the thermoplastic polyimide contains an imidazole ring which can form a complex with copper.

5. The method for preparing a highly adhesive polyimide composite film according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, polycondensing a flexible aromatic diamine, a rigid aromatic diamine and an aromatic dianhydride to generate a polyamic acid resin A; S2, reacting the surface-aminated silica with methyl acrylate or its homologues, and then reacting with aliphatic diamine or its homologues to obtain amino-terminated hyperbranched polyamide grafted silica particles, and finally dispersing the silica particles in a chemical casting reagent, and quickly mixing the silica particles with the polyamide acid resin A prepared in step S1 to obtain a mixed solution; the mass ratio of the surface-aminated silica, acrylate and aliphatic diamine is 1:1-3:0.7-4; S3, polycondensing the diamine, the dianhydride and the monoamine to generate a polyamic acid resin B; S4, using the mixed solution in step S2 as a thermosetting polyimide support layer and the polyamic acid resin B prepared in step S3 as a thermoplastic polyimide adhesive layer, and preparing a polyimide composite film through a film-forming process.

6. The method for preparing a highly adhesive polyimide composite film according to claim 5, characterized in that: In step S2, the amount of the amino-terminated hyperbranched polyamide grafted silica particles added is 0.05%-1% of the mass of the thermosetting polyimide, and the particle size of the amino-terminated hyperbranched polyamide grafted silica particles is 0.1-10 μm.

7. The method for preparing a highly adhesive polyimide composite film according to claim 5, characterized in that: In step S2, the chemical casting reagents are composed of a catalyst, a dehydrating agent and an organic solvent; the catalyst is selected from one or more of pyridine and its derivatives, quinoline, isoquinoline and triethylamine, and the amount of the catalyst is 1-5% of the mass of the polyamic acid resin A; the dehydrating agent is selected from one or more of acetic anhydride, propionic anhydride and benzoic anhydride, and the amount of the dehydrating agent is 15-35% of the mass of the polyamic acid resin A.

8. The method for preparing a highly adhesive polyimide composite film according to claim 5, characterized in that: In step S1, the polyamic acid resin A is prepared by polycondensation of flexible aromatic diamine, rigid aromatic diamine and aromatic dianhydride; the molar ratio of the sum of the molar amounts of the flexible aromatic diamine and the rigid aromatic diamine to the molar amount of the aromatic dianhydride is 100:100.05-100.

5.

9. The method for preparing a highly adhesive polyimide composite film for a flexible copper-clad laminate according to claim 5, characterized in that: In step S3, the monoamine is a monoamine containing an imidazole structure.

10. The method for preparing a highly adhesive polyimide composite film for a flexible copper-clad laminate according to claim 9, characterized in that: The monoamine containing imidazole structure is selected from one or more of 2-aminoimidazole, 4-aminoimidazole, 5-amino-4-imidazolecarboxamide and 2-aminobenzimidazole; the molar ratio of the diamine, dianhydride and monoamine containing imidazole structure is 98-99.5:100:0.5-4.

11. The method for preparing a highly adhesive polyimide composite film according to claim 5, characterized in that: In step S3: The diamine is selected from one or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,3-bis(4'-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and 2,2-bis[4-(4-aminophenoxy)phenyl]propane; The dianhydride is selected from one or more of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride and 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride.

12. A two-layer flexible copper-clad laminate, comprising a copper foil layer and a polyimide layer, characterized in that: The polyimide layer is a highly adhesive polyimide composite film according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Thermoplastic polyimide and method for preparing flexible copper-clad plate from thermoplastic polyimide

    CN103739842A

  • Thermoplastic polyimide film with low thermal expansion coefficient and preparation method thereof

    CN115746351A

  • Method for producing adhesive film

    CN1957051A

  • Thermoplastic polyimide and preparation method of two-layer process adhesive-free double-side flexible copper clad plate using thermoplastic polyimide

    CN102408564A

  • Highly adhesive thermoplastic polyimide resin, polyimide film containing same, and flexible copper clad plate

    CN107698758A

Cited By

  • High-frequency imidization heating device, heating treatment system and heating method for preparing polyimide film

    CN121004704A

  • A high-toughness polyimide composite film for flexible copper-clad plate and a preparation method thereof

    CN122587618A

  • Polyimide-polytetrafluoroethylene composite film, preparation method and application thereof

    CN122628371A